Práticas discursivas em contextos sociais : linguagem e trabalho em uma associação de catadores de materiais recicláveis - Chiaradia, Itatiane (2012)
This interdisciplinary study focuses on the discursive practices of an association of collectors of recyclable materials on the activity work, and aims to describe and analyze how scenography and the discursive ethos are constituted, through the recording of interviews performed with some of the members of the researched group. The guiding theoretical approach is enunciative-discursive of the language of the associative group, emphasizing scenography and the ethos, and with research sources Maingueneau (1997, 2010). In the ergological perspective, Schwartz (1992, 2011) and others studious about this subject like Durrive (2008, 2010) and Trinquet (2010). The work was developed at the Associação Amigos do Meio Ambiente, in the Popular neighborhood of Passo Fundo/RS, an entity made of women residing on the same neighborhood, who work with the recycling of solid residue daily discarded by society, they are also coordinated by the Catholic Church in its many segments. A semi-structured interview and intensive direct observation were used to the execution of the descriptive-bibliographical and documental research, upon the procedure of case study with qualitative approach. Through systematic observation, a plan to organize and record information was developed and used in the following script: observations of written/real work, constituted/invested knowledge, work as activity, rules/renormalizations, dramatics of the self use, and analysis of language practices of the participants of the research. It was attempted to record as many data as possible for further analysis, based on the one which determined that the discursive practices of subjects investigated made it possible to build scenographies from which the discursive ethos was released. The difficulty of the workers to release themselves from taylorist bonds, which prescribe every single work activity, was yet verified.